Bioengineered miRNA-1291 prodrug therapy in pancreatic cancer cells and patient-derived xenograft mouse models. (1st February 2019) - Tu, Mei-Juan; Ho, Pui Yan; Zhang, Qian-Yu; Jian, Chao; Qiu, Jing-Xin; Kim, Edward J.; Bold, Richard J.; Gonzalez, Frank J.; Bi, Huichang; Yu, Ai-Ming
Abstract: Our recent studies have revealed that microRNA-1291 (miR-1291) is downregulated in pancreatic cancer (PC) specimens and restoration of miR-1291 inhibits tumorigenesis of PC cells. This study is to assess the efficacy and underlying mechanism of our bioengineered miR-1291 prodrug monotherapy and combined treatment with chemotherapy. AT-rich interacting domain protein 3B (ARID3B) was verified as a new target for miR-1291, and miR-1291 prodrug was processed to mature miR-1291 in PC cells which surprisingly upregulated ARID3B mRNA and protein levels. Co-administration of miR-1291 with gemcitabine plus nab-paclitaxel (Gem-nP) largely increased the levels of apoptosis, DNA damage and mitotic arrest in PC cells, compared to mono-drug treatment. Consequently, miR-1291 prodrug improved cell sensitivity to Gem-nP. Furthermore, systemic administration of in vivo -jetPEI-formulated miR-1291 prodrug suppressed tumor growth in both PANC-1 xenograft and PC patients derived xenograft (PDX) mouse models to comparable degrees as Gem-nP alone, while combination treatment reduced tumor growth more ubiquitously and to the greatest degrees (70–90%), compared to monotherapy. All treatments were well tolerated in mice. In conclusion, biologic miR-1291 prodrug has therapeutic potential as a monotherapy for PC, and a sensitizing agent to chemotherapy. Highlights: Bioengineered miR-1291 prodrug sensitizes pancreatic cancer cells to chemotherapy. Induction of apoptosis by miR-1291 is associated with the upregulation of ARID3B. MiR-1291 alone suppresses tumor growth in PANC-1 xenograft and PDX mouse models. MiR-1291 augments the efficacy of chemotherapy for pancreatic cancer in vivo.